Bovine embryo sex determination by multiplex loop-mediated isothermal amplification - Trisadee Khamlor (2018)
© 2015 Elsevier Inc. In cattle, the ability to determine the sex of embryos before embryo transfer is beneficial for increasing the number of animals with the desired sex. This study therefore developed a new modification of loop-mediated isothermal amplification in a multiplex format (multiplex LAMP) for highly efficient bovine embryo sexing. Two chromosomal regions, one specific for males (Y chromosome, S4 region) and the other common to both males and females (1.715 satellite DNA), were amplified in the same reaction tube. Each target was amplified by specifically designed inner primers, outer primers, and loop primers, where one of the S4 loop primers was labeled with the fluorescent dye 6-carboxyl-X-rhodamine (emitting a red color), whereas both satellite loop primers were labeled with the fluorescent dye fluorescein isothiocyanate (emitting a green color). After amplification at 63°C for 1hour, the amplified products were precipitated by a small volume of cationic polymer predispensed inside the reaction tube cap. Green precipitate indicated the presence of only control DNA without the Y chromosome, whereas orange precipitate indicated the presence of both target DNAs, enabling interpretation as female and male, respectively. Accuracy of the multiplex LAMP assay was evaluated using 46 bovine embryos with known sex (25 male and 21 female) generated by somatic cell nuclear transfer and confirmed by multiplex polymerase chain reaction. The multiplex LAMP showed 100% accuracy in identifying the actual sex of the embryos and provides a fast, simple, and cost-effective tool for bovine embryo sexing.